Intra‐aortic balloon pump: is the technique really outdated? - Mariama Akodad; Clément Delmas; Laurent Bonello; Claire Duflos; François Roubille (ESC Heart Failure)
Abstract Aims Intra‐aortic balloon pump (IABP) utilization was expected to be quickly abandoned following the IABP‐shock trial and its class III, level B recommendation in the 2016 European Society of Cardiology (ESC) guidelines. The aim of this study was to evaluate the use of IABP compared with other mechanical support devices in a nationwide approach. Methods and results We conducted a retrospective study based on the French national hospital discharge database. All patients undergoing assist device implantation by IABP, extracorporeal membrane oxygenation (ECMO), or IMPELLA® from 2014 to 2018 (2 years before/2 years after the 2016 guidelines) were included. The primary endpoint was the incidence of IABP implantation over the years. Secondary endpoints were incidence of total assist device, ECMO, and IMPELLA® implantations. From 2014 to 2018, a total of 18 940 patients benefited from mechanical support by IABP (n = 6657, 35.2%), ECMO (n = 11 881, 62.7%), or IMPELLA® (n = 402, 2.1%) in France. The incidence of total mechanical support implantations (ECMO and IABP) was constant over the years. IABP implantations decreased progressively from 1725 implantations in 2014 to 996 in 2018 (−42%). By contrast, ECMO implantations increased progressively from 1919 implantations in 2014 to 2763 implantations in 2018 (+44%). IMPELLA® implantations remained stable over the years from 63 (1.7%) implantations in 2014 to 83 (2.1%) in 2018. Conclusions In this nationwide real‐life study, despite a significant decline in IABP implantations over the years since the ESC guidelines, this device remained used in clinical practice with around 1000 implantations in 2018. The size of centres was not strictly correlated with this use, suggesting differential uses depending on the local background.